2010
DOI: 10.4141/cjas09115
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between backfat thickness and reproductive efficiency of sows: A two-year trial involving two commercial herds fixing backfat thickness at breeding

Abstract: . 2010. Relationships between backfat thickness and reproductive efficiency of sows: A two-year trial involving two commercial herds fixing backfat thickness at breeding. Can. J. Anim. Sci. 90: 429Á436. In this study, we established whether controlling backfat thickness at breeding over a long time period can result in optimized reproductive performance in sows. Two commercial herds were used: herd A (322 purebred Landrace sows) and herd B (337 cross-bred Yorkshire-Landrace sows). Backfat thickness at breeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 17 publications
3
23
0
Order By: Relevance
“…Reduced subsequent reproductive performance occurs because of either an insufficient amount of body reserves at farrowing or restricted feed intake during lactation. These points collectively show the importance of mobilisable body reserves that can be used during lactation without influencing reproductive performance, such as the weaning-to-oestrus interval (Houde et al 2010). As shown in this study, the higher body reserves at farrowing reduce voluntary feed intake and increase weight loss during lactation.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Reduced subsequent reproductive performance occurs because of either an insufficient amount of body reserves at farrowing or restricted feed intake during lactation. These points collectively show the importance of mobilisable body reserves that can be used during lactation without influencing reproductive performance, such as the weaning-to-oestrus interval (Houde et al 2010). As shown in this study, the higher body reserves at farrowing reduce voluntary feed intake and increase weight loss during lactation.…”
Section: Discussionsupporting
confidence: 58%
“…In the present study, both body weight change and backfat change were decreased in sows in the FFT group and in sows with lower backfat thickness in hot weather. It is widely recognised that the backfat thickness and body conditions of sows affect the subsequent reproductive performance of sows (Houde et al 2010;Strathe et al 2017). Higher variation in feed intake feeding pattern and milk production increases the variation in backfat thickness and losses of backfat levels at weaning (Maes et al 2004;Strathe et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study also showed that dietary supplementation of DL-Met and OH-Met during lactation did not affect the body weight and backfat thickness of sows, but the loss of body weight and backfat during lactation was not calculated [15]. Because loss of body weight and backfat during lactation reduces subsequent reproductive performance [28,29], the present study offers the first evidence that dietary supplementation of OH-Met during later gestation and lactation benefits body energy metabolism and can potentially improve the reproduction of sows. Likewise, dietary supplementation of DL-Met and(or) OH-Met increased the body weight gain of piglets during day 0-7 and day 7-14.…”
Section: Discussionmentioning
confidence: 98%
“…None of the treatments affected backfat thickness at any period of evaluation (P > 0.05). According to Houde et al (2010), fluctuations in backfat thickness during the reproductive cycle should be avoided, as it is associated with declining reproductive performance over subsequent parities. However, the tendency to be different (P = 0.060) in percentage between the evaluation at d 53 and 25 indicates that sows receiving Rac could have greater lipid catabolism or a lower lipogenesis than the sows of the other treatments, as the nutritional management of the farm provided less nutrients than recommended by Rostagno et al (2011) during gestation phase.…”
Section: Sow Performancementioning
confidence: 99%